Head movements induced by voluntary neck flexion stabilize sensorimotor synchronization of the finger to syncopated auditory rhythms - Yamazaki, Ryoichiro; Ushiyama, Junichi (Frontiers in Psychology, 2024)
Head movements that are synchronized with musical rhythms often emerge during musical activities, such as hip hop dance. Although such movements are known to affect the meter and pulse perception of complex auditory rhythms, no studies have investigated their contribution to the performance of sensorimotor synchronization (SMS). In the present study, participants listened to syncopated auditory rhythms and flexed their dominant hand index finger in time with the perceived pulses (4/4 meters). In the first experiment (Exp. 1), the participants moved their heads via voluntary neck flexion to the pulses in parallel with finger SMS (Nodding condition, ND). This performance was compared with finger SMS without nodding (Without Nodding condition, WN). In the second experiment (Exp. 2), we investigated the specificity of the effect of head SMS on finger SMS confirmed in Exp. 1 by asking participants to flex their bilateral index fingers to the pulses (Bimanual condition, BM). We compared the performance of dominant hand finger SMS between the BM and ND conditions. In Exp. 1, we found that dominant hand finger SMS was significantly more stable (smaller standard deviation of asynchrony) in the ND versus WN condition (p < 0.001). In Exp. 2, dominant hand finger SMS was significantly more accurate (smaller absolute value of asynchrony) in the ND versus BM condition (p = 0.037). In addition, the stability of dominant hand finger SMS was significantly correlated with the index of phase locking between the pulses and head SMS across participants in the ND condition (r = –0.85, p < 0.001). In contrast, the stability of dominant hand finger SMS was not significantly correlated with the index of phase locking between pulses and non-dominant hand finger SMS in the BM condition (r = –0.25, p = 0.86 after multiple comparison correction). These findings suggest that SMS modulation depends on the motor effectors simultaneously involved in synchronization: simultaneous head SMS stabilizes the timing of dominant hand finger SMS, while simultaneous non-dominant hand finger SMS deteriorates the timing accuracy of dominant hand finger SMS. The present study emphasizes the unique and crucial role of head movements in rhythmic behavior.